Neo-Ibuism in Education: Representation of Femininities in Indonesian EFL Textbooks for Junior High School Students - Nafis, Rifqi Nasirun; Eliyanah, Evi; Yannuar, Nurenzia (Institut Agama Islam Negeri (IAIN) Curup, 2025)
EFL textbooks play a crucial role in building sociocultural understanding for young learners, particularly in developing their perspectives and perceptions of gender. This study systematically and critically examines how representations of femininity emerge in Indonesian EFL textbooks for junior high school students. Using Critical Discourse Analysis (CDA), this study examines how femininity is discursively constructed through various textual and visual sources. Referring back to the Critical Discourse Analysis (CDA) framework proposed by Fairclough (1995), this study critiques and analyzes how women, including girls, are portrayed in these textbooks, particularly in social contexts such as family, work, and community life. The findings highlight that some Indonesian EFL textbooks, particularly for junior high school students, predominantly reinforce traditional gender norms, strongly aligned with Neo-Ibuism. This contemporary discourse idealizes women as dedicated mothers and caregivers, while at the same time providing them with opportunities to have professional and leadership roles, albeit in limited areas. Such representation, while promoting a limited change, still risks perpetuating gender stereotypes that normalize multiple burdens for women. This study implies the need for more inclusive and diverse portrayals of femininity in educational materials to support the promotion of gender equality in Indonesian classrooms and, more broadly, Indonesian education.